Hubungan Penyebaran Informasi Pendidikan Seks Dengan Perilaku Orang Tua Di Desa Banjurpassar - Pratiwi, Diana Rizki; Winoto, Yunus (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
This study aims to determine the relationship of the spread of sex education information with the behavior of parents in explaining about sex in adolescents. The variables in this study consisted of independent variables, namely the dissemination of information which includes aspects of communicators, messages and media and the dependent variable, namely the behavior of parents in explaining sex education. The location of the study was conducted in Banjurpassar Village which is one of the village areas in the coastal area of Kebumen Regency. The approach used in this study uses a quantitative approach to the type of correlation research. The population in this study are parents who participated in counseling about sex education provided by the District Health Office, Kebumen. As for the technique of sampling, it uses simple random sampling technique. The data collection techniques are carried out through questionnaires, interviews, observations and through library studies. As for the analysis of data using descriptive statistical analysis and inferential statistical analysis. Based on the results of hypothesis testing it is known that for minor hypotheses it is known that all aspects tested, namely the communicator, message and media aspects have a significant relationship with the behavior of parents in providing sex education to adolescents, so in general based on Maior hypothesis testing it can be said that the dissemination activities information about sex education has a significant relationship with the ability of parents to explain about sex in their teenage children. From the results of this study it can be concluded that the dissemination of information about sex education through counseling activities to parents is very effective in explaining about sex in young children.